Designing Learning Translation Using the Motifs of Anyaman Bambu - Maryati Maryati; Rully Charitas Indra Prahmana (IndoMath: Indonesia Mathematics Education, 2020)
Indonesia has many cultures, one of which is in the form of traditional crafts namely Anyaman Bambu. It’s a form of traditional craft in the community that uses bamboo as its basic material. However, people only see these crafts as only a form of traditional craft, even though there are many motifs in these crafts that can be used as a starting point in learning mathematics, namely geometry transformations. Therefore, this research aims also to produce the learning trajectory of students in learning one subject in geometry transformations namely translation, which develops from informal to formal level through the Indonesian Realistic Mathematics Education (IRME) approach. The research method used is design research starting from preliminary design, design experiments, and retrospective analysis. This study explores how the motifs of Anyaman Bambu make a real contribution for ninth-grade students to understand the concept of translation. The results of design experiments show that the context of the motifs of Anyaman Bambu can stimulate students to understand their knowledge of the concept of translation. All the strategies and models that students find, describe, and discuss that show how students' constructions or contributions can be used to help their initial understanding of the translation.